Dampak Pendidikan Kewirausahaan dan Motivasi Wirausaha Terhadap Minat Berwirausaha - Sigit Teguh; Dies Nurhayati (Universitas Pendidikan Ganesha, 2026)
Entrepreneurship can be a solution to reduce the unemployment rate in a country, including in Indonesia. However, to encourage one's entrepreneurial spirit, support from both academic and non-academic sides is needed. The main highlight in this study is to foster interest in entrepreneurship, especially for students. Entrepreneurship and Motivation Education are factors that can encourage students' entrepreneurial interest. Providing Entrepreneurship Education, especially in the University environment, is expected to be able to provide motivation for students to start starting a business. This research was written using the literature review method to summarize various studies and discoveries that have been carried out previously. This research was carried out by examining references in the form of articles and books related to Entrepreneurship. There are 10 (ten) articles used as references in this study. Almost all references use quantitative methods, using research instruments in the form of questionnaires for data collection. The data collection process was carried out online and offline to certain respondents in accordance with the criteria in the study. This study and previous research showed the results that Entrepreneurship and Motivation Education affects students' entrepreneurial interests, but there is one reference that shows that there is no influence of Entrepreneurship Education on entrepreneurial interest. This is because in the study, the respondents felt that the provision of Entrepreneurship Education was only limited to fulfilling lecture obligations. In addition, several references add other variables that can trigger the emergence of student entrepreneurial interest.